2021
DOI: 10.1093/infdis/jiab092
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Molecular Testing in Pediatric Meningitis Surveillance in Southern and East African Countries, 2008–2017

Abstract: Background As part of the global Invasive Bacterial Vaccine-Preventable Diseases Surveillance Network, 12 African countries referred cerebrospinal fluid (CSF) samples to South Africa’s regional reference laboratory. We evaluated the utility of real-time polymerase chain reaction (PCR) in detecting and serotyping/grouping Haemophilus influenzae, Neisseria meningitidis, and Streptococcus pneumoniae (HNS). Methods From 2008 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Regardless of the germ found in CSF, elevated white blood cell count and CRP that were more likely to be PCR bacterial positive than samples without these characteristics in our study group, similar results has been observed in many African countries as described by Mignon du Plessis and Coll [25].…”
Section: Discussionsupporting
confidence: 90%
“…Regardless of the germ found in CSF, elevated white blood cell count and CRP that were more likely to be PCR bacterial positive than samples without these characteristics in our study group, similar results has been observed in many African countries as described by Mignon du Plessis and Coll [25].…”
Section: Discussionsupporting
confidence: 90%